Quantitative assessment of reflected light characteristics on solar panel - Piroska Víg (Results in Engineering)
When using solar panels, the appearance of the surfaces results in a change in the optical parameters of our environment. The solar panel and the PV/T collector can change the intensity of the radiation, the spectrum and the polarization of the light, which has a serious effect on living organisms sensitive to these parameters. The present article examines these optical effects of solar panels and investigates how close they are to the optical effect produced by water surfaces. Under artificial lighting, in laboratory conditions, it examines the dependence of the spectrum, intensity and polarization of the light reflected from the solar panel on the angle of incidence. Based on the measurement data, it can be stated that the approximation is the greatest at an elevation angle of around 40° and this also results in the similarity of the polarization for this range in the case of the two surfaces. The obtained numerical results are also supported by measurements in a natural environment. The results of the research are important for the expectations regarding the properties of special nanotechnology coatings applied to solar surfaces.